Differential Protein Contents in Two Members of the White fly Bemisia tabaci(Hemiptera:Aleurodidae)Complex:Reproductive and Invasive Implications - Dieng, Hamady; Ahmad, A.Hassan; Satho, T.; Che Salmah, Md Rawi; Aziz, A. Thabani; Miake, Fumio; Vargas, R.E. Morales; Morales, P.; Ahmad, H.; Saad, A. Ramli; Rajen, S.; Abu Bakar, S. (Maxwell Scientific Organization, 2013)
Abstract: Although the displacement of some native whitefly species by he B biotype of Bemisia tabaci ha been noted in China, it is still unclear physiological and molecular mechanisms predominate during such invasions. Here, we investigated proteome varialibility in both B biotype and the native ZHJI haplotype.ZHJI eggs showed larger numbers of specific proteins than B eggs. A set of proteins found in B eggs were present at higher levels in ZHJI.Three ZHJI egg proteins were present at higher levels in B eggs. ZHJI males possessed four specific proteins, and at least five other male proteins were shared by two whiteflies.Two proteins identified in ZHJI males were present at higher levels in B males. Three other shared male proteins weere found at much higher levels in ZHJI than in the B biotype. Both ZHJI and B expressed three specific female proteins. Most of the female proteins identified in ZHJI were present at much higher levels in B. In conclusion, protein content indexed by electrophoretic profiling has likely played an important role during the displacement of natives by the B biotype.